Constructing Agile Islamic Educational Leadership in Responding to Learning Ecosystem Disruption in the Digital Era - Kenny Agusto Arie Wibowo; Syukron Darsyah; Kadar Risman; Mulyadi (Institut Bahri Asyiq Galis Bangkalan, 2025)
The disruption of learning ecosystems in the digital era has fundamentally restructured interaction patterns, organizational structures, and pedagogical practices within educational institutions, including Islamic education. Rapid digital transformation has required leadership models that are adaptive while remaining grounded in Islamic values. This study aimed to construct a conceptual framework of agile Islamic educational leadership in responding to the dynamics of digital learning disruption. The research employed a descriptive qualitative approach through a Systematic Literature Review of scientific publications from 2016 to 2025 retrieved from the Scopus, Google Scholar, and Sinta databases. Data were collected through systematic digital documentation and analyzed using content analysis and thematic analysis. The findings indicated that agile Islamic educational leadership was developed through the integration of organizational adaptability, data-driven decision making, digital collaboration, teacher capacity development, and a digital vision grounded in the principles of amanah, shura, and justice. This construction expanded the paradigm of educational leadership by integrating agility theory with Islamic values and provided practical guidance for sustainable digital transformation in Islamic educational institutions.